The implementation of safety management at Setia City Mall, Shah Alam / Siti Aishah Shamsuddin - Shamsuddin, Siti Aishah (Faculty of Architecture, Planning and Surveying, 2015)
Safety management in shopping mall is very important as many people go there for many purposes. This is because mainly accidents happen without knowing time or places. Nowadays, the number of accidents happens in shopping mall increased and it really becomes a serious matter to be considered. Accidents may not only give negative effects to the people inside and at the surrounding of the mall but it also gives impacts to the prestige of the mall itself. It shows how the management are in keeping with the image of the mail’s organisation. In response to the importance of safety management, the objectives of this research are to study the concept of safety management in the shopping malls, to investigate the variety scopes of safety management that implemented at Setia City Mall and to obtain the satisfaction level of visitors towards the public safety and security within the selected shopping mall environment. The data collected can be categorised as primary data and secondary data. This method shall be used to analyse the data obtained and therefore, conclusion and recommendations will be drawn to summarize the findings. The respondents for this dissertation are the safety management team and the public whether they are the visitors or workers of the shopping mall. Throughout this research, safety measures can be planned at the early stage and during the operation of mall since prevention is better than cure. This research is really important especially to the management team in order to know their responsibilities are done well or not and to improve their safety measures by collecting the level of satisfaction of their visitors. This research thesis will be benefit to acknowledge the standard of safety management in shopping malls. Respectively the qualitative output of the research i.e. the impacts, consequences and recommendation; alternative solutions to the mall management will endeavour to move in future by implementing the resulting strategies to bring out the delectable changes in the management’s ability.